Co- teaching in the differentiated classroom : successful collaboration, lesson design, and classroom management - Fattig, Melinda L.; Taylor, Maureen Tormey (A wiley imprint : Jossey Bass, 2008)
This book offers an approach for managing students with diverse abilities and needs in the overcrowded K-12 classroom. Based on an award-winning collaboration model, the book shows how special education teachers can pair with mainstream teachers to improve classroom functioning while promoting high achievement for all students.
includes bibliographical references and index.
Keywords: Teaching teams; individualized instruction; lesson planning; Classroom management; Education, Secondary